GESTIÓN DE LA INFORMACIÓN EN EMERGENCIAS: COMUNICACIÓN DE MALAS NOTICIAS AL ENTORNO CERCANO EN CASOS DE PERSONAS DESAPARECIDAS POR PARTE DE LOS PROFESIONALES DE LA SEGURIDAD Y LAS EMERGENCIAS. - Álvarez Aparicio, Ana Isabel (Revista de Comunicación y Salud, 2025)
Introduction: every year in Spain there are an average of 20,000 reports of missing persons. The pain and uncertainty they generate have an impact on many different levels. Relatives and friends of the missing person are some of the most affected. Knowing how to adequately communicate information that is known to be adverse to the closest environment by security and emergency professionals is considered essential due to its possible positive implications for both parties. Objective: this article aims to demonstrate the importance of correct communication of bad news to the immediate environment in cases of missing persons by security and emergency professionals, as well as the need for studies and research that delve into the effectiveness of specific protocols on the matter that facilitate adaptive coping with the situation. Methodology: a review was carried out based on the scientific evidence collected in the existing literature on the subject. The databases PubMed, Scopus, and the Google Scholar search engine were consulted. Results: bad news, when a person disappears, occurs at different times and at different levels. Security and emergency professionals must be trained not only to transmit information to the missing person's environment, but also so that they are able to then transfer it to their own environment in the most appropriate, efficient and effective way possible, reducing the resulting psychological and emotional impact as much as possible. Conclusion: the adequate transmission of adverse information requires good communication skills and adequate management of basic technical guidelines for action, as well as the adaptation of communication to the prevailing reality at each moment and situation. The development of specific protocols can facilitate adaptation and coping processes. Studies are needed to shed light on this issue.